The rehabilitation of drug addicts at a Christian centre in Selangor / Siet Fong Chong - Siet , Fong Chong (1983)
Fieldwork was conducted at a Christian drug rehabilitation centre in Selangor (New Life) and lasted for 2 months. This study aims to examine the rehabilitation process at a Christian drug rehabilitation centre. Although studies have been conducted on government rehabilitation centres, nothing much is known of Christian based drug rehabilitation programme. In chapter I, I have listed the aim of study, methodology and the problems and limitations of this study. I have given a brief account of its background and physical structures of the centre in chapter II. Also are the criteria for intake and the rules and regulations of New Life Centre. In the following chapter, is enlisted the duties and responsibilities of the administrators and the administration of the centre as a whole. I shall also discuss its grading system and success rate. The linkage of New Life to the Church and its activities will also be mentioned. Chapter IV discusses the societal reaction towards drug addiction and its consequences. The resocialization process, the problems encountered in the process and how these problems can be overcome is seen in this chapter. In chapter V, I aimed to reveal the profiles of drug addicts of different ethnic and social-economic background. I shall possible reason for their drug addiction. In concluding, I shall bring forward implications and weakness of New Life as well as suggest recommendations that may help to improve the present rehabilitation efforts.